2023
DOI: 10.3390/foods12051014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Isopanduratin A on Adipogenesis: A Study of Possible Mechanisms

Abstract: The root of Boesenbergia rotunda, a culinary plant commonly known as fingerroot, has previously been reported to possess anti-obesity activity, with four flavonoids identified as active principles, including pinostrobin, panduratin A, cardamonin, and isopanduratin A. However, the molecular mechanisms underlying the antiadipogenic potential of isopanduratin A remain unknown. In this study, isopanduratin A at non-cytotoxic concentrations (1–10 μM) significantly suppressed lipid accumulation in murine (3T3-L1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…This indicated that low concentration of isopanduratin A could reduce cellular fat accumulation in human preadipocytes. 19) Therefore, treatment of 3T3-L1 adipocytes with BP-3 extract at the concentrations of 1 to 10 µg/mL during adipogenesis markedly decreased triglyceride accumulation without cytotoxicity, indicating that the anti-obesity potential of BP-3 extract can reduce adipogenesis and lipid accumulation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This indicated that low concentration of isopanduratin A could reduce cellular fat accumulation in human preadipocytes. 19) Therefore, treatment of 3T3-L1 adipocytes with BP-3 extract at the concentrations of 1 to 10 µg/mL during adipogenesis markedly decreased triglyceride accumulation without cytotoxicity, indicating that the anti-obesity potential of BP-3 extract can reduce adipogenesis and lipid accumulation.…”
Section: Discussionmentioning
confidence: 82%
“…2) Additionally, the mechanism of the lipolytic action of isopanduratin A have been reported as the suppressive effect on 3T3-L1 adipogenesis by downregulating adipogenic effectors (fatty acid synthase (FAS), perilipin 1 (PLIN1), lipoprotein lipase (LPL), and adiponectin) and adipogenic transcription factors (sterol regulatory element-binding protein 1c (SREBP-1c), peroxisome proliferator-activated receptor γ (PPARγ), and CCA AT/enhancer binding protein α (C/EBPα)), which these lipid metabolism proteins are essential for maintaining cellular lipid homeostasis and associated with metabolic conditions such as hyperlipidemia, insulin resistance, atherosclerosis, and obesity. 19) BP-3 extract-loaded MS serum was successfully formulated with a good appearance and smooth texture upon application onto the skin. MS serum strongly increased the skin permeability of panduratin A, because microneedling can create transportation routes for many compounds through the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Isopanduratin A and other phytochemicals positively affect fat formation through activation of the AMP-activated protein kinase (AMPK)-acetyl-CoA carboxylase (ACC) pathway. Isopanduratin A causes dephosphorylation of p-ERK/ERK signaling, which slows adipogenesis in 3T3-L1 cells by inducing growth arrest [ 38 , 39 ]. However, the specific processes involved in the regulation of MCE during adipogenesis by LAB remain unclear.…”
Section: Discussionmentioning
confidence: 99%